1987
DOI: 10.1523/jneurosci.07-05-01586.1987
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of neurofilament proteins and chromatolysis following transection of rat sciatic nerve

Abstract: States of phosphorylation of neurofilament proteins were examined in the perikarya of rat sensory and motor neurons between 3 and 28 d following either a distal transection [6–7 cm from the L4-L5 dorsal root ganglia (DRG)] or a proximal transection (1–2 cm from the L4-L5 DRG) of the sciatic nerve. Paraffin sections of the right (experimental) and left (control) L4 and L5 DRG from animals with unilateral transection of the right distal sciatic nerve were stained immunocytochemically with monoclonal antibodies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…The axonal atrophy and loss were not associated with a significant change in neuronal density in the anterior horn of the spinal cord, suggesting that axons had degenerated in a number of these neurons but that their cell bodies were still present. This hypothesis is supported by the accumulation of phosphorylated neurofilaments in perikarya of spinal cord motor neurons in Tg30tau mice, an event known to be associated with a variety of axonal insults, including axonal transection 62,63 and several neurodegenerative diseases, 64 such as classic amyotrophic lateral sclerosis, 65 Guam amyotrophic lateral sclerosis/parkinsonismdementia complex 48 and transgenic models. 66 Axonal spheroids were numerous in Tg30tau mice and appeared even earlier than NFTs.…”
Section: Axonal Atrophy Axonal Loss and Spheroids As Evidence Of Eamentioning
confidence: 92%
“…The axonal atrophy and loss were not associated with a significant change in neuronal density in the anterior horn of the spinal cord, suggesting that axons had degenerated in a number of these neurons but that their cell bodies were still present. This hypothesis is supported by the accumulation of phosphorylated neurofilaments in perikarya of spinal cord motor neurons in Tg30tau mice, an event known to be associated with a variety of axonal insults, including axonal transection 62,63 and several neurodegenerative diseases, 64 such as classic amyotrophic lateral sclerosis, 65 Guam amyotrophic lateral sclerosis/parkinsonismdementia complex 48 and transgenic models. 66 Axonal spheroids were numerous in Tg30tau mice and appeared even earlier than NFTs.…”
Section: Axonal Atrophy Axonal Loss and Spheroids As Evidence Of Eamentioning
confidence: 92%
“…Following axotomy the synthesis, axonal transport of NFP, and the expression of mRNA of NFP decrease (13,14,22,23,35), and the NFP accumulated in the neurons suggest that, as least for NFP, the transport is blocked at the level of cell body (27). In addition, it is probable that the enhanced perikaryal phosphorylation of NFP represents part of the chromatolytic response to axonal injury (11,17), but we have not seen signs of chromatolysis in the NFP IR neuronal somata. In spite of this evidence, Dahl et al (6) affirm that the stain patterns of lumbar DRG for NFP remain unchanged after sciatic nerve crush and ligature, and recently Troy et al (32) did not find changes in phosphorylation independent NF 160 kD epitope for a 6 week period of study in rat spinal motor neurons.…”
Section: Animalsmentioning
confidence: 59%
“…In addition, Vickers and Costa ( In the present study we have found that the number of primary sensory neurons showing detectable NFP-IR in the perikarya, as well as the intensity of IR, increases in a time-dependent manner for 2 weeks after axotomy. Goldstein et al (11) NSE-IR neurons of L5 DRG one (Fig. 10), three ( Fig.…”
Section: Animalsmentioning
confidence: 95%
“…Hyperplasia is indicated by an abnormal increase in the number of organic tissue, while hypertrophy is the increase in cell size 19 . These changes may be physiologic or pathologic, and usually result from increase demand, chronic inflammatory response, hormonal dysfunction or compensation for damage or disease elsewhere 20 , which may affect the function of the medial prefrontal cortex. Loss of cortical cellular membranes was also observed in the test groups indicating delipidization, which is also a prelude to degeneration and this may imply that the hyperplasia and hypertrophic changes may be pathological.…”
Section: Discussionmentioning
confidence: 99%